Mobilising social network support: the case of Polish migrant mothers in Dublin - Bojarczuk, Sara Marta (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Sociology, 2021)
As international mobility has increased over the last decades, so has research on transnational families and transnational care, gaining a more prominent place in family and migration research. Following the expansion of the European Union (EU) in 2004, Irish migratory scene has changed dramatically. Within a few years, Polish immigrants had established themselves as the largest immigrant group in Ireland (122,515 according to the Census in 2016) and have increasingly attracted greater attention across academic research. However, most research has focused on integration, employment and career aspirations, rarely considering not only their families but also how migrant women organise their lives in the new country. This study aims to contribute to the growing field of research on migrants social support, both transnationally and locally, with an account of the female perspective. Grounded in a support network perspective, the study employs a mixed methods approach to elucidate how migrant mothers use local, transnational and online relations in their social support mobilisation strategies, mainly in childcare as the crucial tangible type of support, but also other intangible dimensions such as emotional, acquisition of information and those involving socialising.Moreover, the original mixed-method design of this study aims to provide a unique contribution to the field of social support networks. Through 61 in-depth, semi-structured interviews, accompanied by a visual mapping of participants social networks, this thesis describes utilisation of support networks among Polish migrant working mothers for various types of support in light of their return to work and the process of managing childcare and employment in a foreign country, where the availability of friends and relatives is limited. Through an original mixed methods approach, the data analysis provides both an inductive qualitative account of the mechanisms behind organising such support, and a quantitative analysis (created through a quantification process) assessing the general trends within the sample in a systematic manner. It is concluded that community ties with friends and family are the principal means by which people receive supportive resources from others. It is shown that the support mobilisation strategies are greatly on the geographical distance and the strength of the relationship. While strong ties are proven invaluable in providing emotional and instrumental support (mainly prolonged childcare), this thesis proves that distance matters and it shapes the way that mothers mobilise their networks to provide support at the time, when transnational support in not available. Locally-based weak ties, based on various forms of reciprocity, are supplemental in sourcing ad-hoc crisis support when transnational ties cannot be mobilised. Nonetheless, transnational ties are shown to be crucial in childcare provision, in particular for longer spells of regular childcare and for emotional support. Additionally, it is argued that Facebook groups, in particular, provide mothers with invaluable opportunities to form virtual communities based on mutual support.
APPROVED
Keywords: transnational migration; social support; childcare; Polish migrants; migrant mothers; migration; gender; mixed methods; Quantitative; Qualitative; Generalisation model; social networks